Rhodomyrtone as a New Natural Antibiotic Isolated from Rhodomyrtus tomentosa Leaf Extract: A Clinical Application in the Management of Acne Vulgaris - Wunnoo, Suttiwan (Antibiotics (Basel), 2021)
Rhodomyrtone, a plant-derived principal compound isolated from Rhodomyrtus tomentosa (Myrtaceae) leaf extract, was assessed as a potential natural alternative for the treatment of acne vulgaris. The clinical efficacy of a 1% liposomal encapsulated rhodomyrtone serum was compared with a marketed 1% clindamycin gel. In a randomized and double-blind controlled clinical trial, 60 volunteers with mild to moderate acne severity were assigned to two groups: rhodomyrtone serum and clindamycin gel. The volunteers were instructed to apply the samples to acne lesions on their faces twice daily. A significant reduction in the total numbers of acne lesions was demonstrated in both treatment groups between week 2 and 8 (p < 0.05). Significant differences in acne numbers compared with the baseline were evidenced at week 2 onwards (p < 0.05). At the end of the clinical trial, the total inflamed acne counts in the 1% rhodomyrtone serum group were significantly reduced by 36.36%, comparable to 34.70% in the clindamycin-treated group (p < 0.05). Furthermore, a commercial prototype was developed, and a clinical assessment of 45 volunteers was performed. After application of the commercial prototype for 1 week, 68.89% and 28.89% of volunteers demonstrated complete and improved inflammatory acne, respectively. All of the subjects presented no signs of irritation or side effects during the treatment. Most of the volunteers (71.11%) indicated that they were very satisfied. Rhodomyrtone serum was demonstrated to be effective and safe for the treatment of inflammatory acne lesions.